The Relationship Between Exclusive Breastfeeding And Weight Faltering In Toddlers - Fara Khansa Azizah (International Journal of Health Sciences, 2025)
Weight Faltering is a condition where a toddler's weight growth is stunted, which can impact their nutritional status and long-term health. One important factor influencing toddler growth is exclusive breastfeeding during the first six months of life. This study aims to determine the relationship between exclusive breastfeeding and the incidence of weight gain. faltering in toddlers. This study used a quantitative analytical design with a cross-sectional approach. The study sample consisted of 80 toddlers aged 6–24 months selected using a purposive sampling technique. Data were collected through interviews using questionnaires and toddler weight measurements based on the Health Card (KMS). Data analysis was performed using the Chi- Square test. The results showed a significant relationship between exclusive breastfeeding and the incidence of weight loss. faltering in toddlers with a p value < 0.05. Toddlers who do not receive exclusive breastfeeding have a higher risk of experiencing weight gain. faltering. The conclusion of this study shows that exclusive breastfeeding plays an important role in preventing weight gain. faltering in toddlers.